Hak Perempuan Dalam Memilih Calon Suami Ditinjau dari Perspektif Madzhab Syafi’i dan Madzhab Maliki - Heriyansah Nst; Juni Fatimah Arsyita; M Aldi Tanjung; M Herry Samzidane; M. Zaitun; Putri Syifa Fazyra (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The problem raised in this research is to give freedom to women in choosing a future husband. In general, this can be put forward in the thinking of people whose relationships are still traditional, marriage is suggested as a necessity for every human being who has a desire for this because of encouragement from the closest person or is part of the inheritance of social traditions. This article also aims to find out the views of several Maliki and Syafi'i schools regarding women's freedom in choosing a husband-to-be. The choice of a husband-to-be is part of a woman's rights absolutely or there is interference from her parents. Because the incidents of arranged marriages and the practice of forced marriages by parents are still often encountered in everyday life in Indonesian society. The Syafi'i and Maliki schools have different opinions regarding women's freedom in choosing a husband. In the Syafi'i school, it is argued that for immature girls, a father, in this case, according to him, may interfere in choosing a future husband even without his permission, and for women who are married and then divorced (widows), according to him, there must be clear approval from concerned. Meanwhile, according to the Maliki school of thought, he argued that women are obliged to marry prospective husbands who are willing and have religion and good behavior, otherwise it will make a person a maker of slander and violence on earth. piety and piety Key Words: Women, Freedom To Choice Husbands, Parents, Madzhab Syafi’I And Madzhab Maliki